INTERNALISASI PENGASUHAN AYAH BERLATAR BELAKANG PENDIDIKAN PESANTREN DALAM PENDIDIKAN SEKSUAL ANAK DI DESA GUNUNGSARI KECAMATAN BANSARI - Ifadah, luluk; Susilo, Farid Hasyim; Ulya, Rimatul; Ananda, Riskya (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
This research is motivated by the rise of sexual crimes in the community due to the lack of sexual education that children receive in the family environment. In addition, in general, the responsibility for caring for children’s sexual education is given more to the mother, even though the position of the father plays a significant role in providing comprehensive and implementable sexual education for children. , especially if the father has a boarding school education background that has adequate religious knowledge. So, the purpose of this research is to know the internalization of methods and materials for parenting fathers with Islamic boarding schools backgrounds through sexual education in children as well as knowing the obstacles encountered in parenting patterns of child sexual education and the solutions implemented to overcome these obstacles. This type of research is ield research with qualitative methods using a phenomenological approach while the primary data source in this study is fathers with a background in Islamic boarding schools in Gunungsari Village. The results of this study are the first method used by a father with a pesantren background in his child’s sexual education. Direct instruction, applying an attitude of responsibility and discipline and firmness, giving sanctions, working with his wife and giving direct examples. As for the material provided; thoharoh, puberty, dress and association ethics. The two obstacles faced are the lack of communication about sex education and the gender bias construction of mother-centred sexual education. The three solutions are provided through approaches and communication that are closer and more familiar to children in their daily activities, familiarizing fathers’ involvement in caring for children’s sexual education Keywords: Father’s parenting, Islamic boarding school education background, sexual education